Public Health Preparedness and Response: Lessons Learned from Recent Global Health Crises - Lovelin Auguskani, Jerlin Priya (Journal of Neonatal Surgery, 2025)
Recent global health crises, including the COVID-19 pandemic, Ebola outbreaks, and the Zika virus, have underscored the critical importance of public health preparedness and response. This paper examines key lessons learned from these events, highlighting the role of early detection, rapid response, international collaboration, and resilient healthcare systems. The analysis explores challenges such as misinformation, resource allocation, and disparities in healthcare access while identifying best practices for improving future outbreak preparedness. Strengthening public health infrastructure, investing in research and development, and fostering community engagement are crucial to mitigating the impact of future pandemics. By learning from past crises, policymakers and health organizations can develop more effective strategies to protect global health security.